Pengaruh Flash sale terhadap Impulse buying: Peran Emosi Positif sebagai Mediator pada pengguna Aplikasi Shopee - Ramadhan, M. Rohim; Wardi, Yunia (SAFE-Network, 2025)
The rapid growth of e-commerce has intensified the phenomenon of online impulse buying, particularly through promotional strategies such as flash sales. This study aims to examine the effect of flash sales on online impulse buying with positive emotion as a mediating variable. Employing a quantitative explanatory approach, data were collected from 130 active students of the Faculty of Economics and Business at Universitas Negeri Padang who had participated in flash sale programs on the Shopee platform. Data analysis was conducted using Partial Least Squares Structural Equation Modeling with the SmartPLS software. The results research show that flash sales have a significant and positive effect on online impulse buying, both directly and indirectly through positive emotion. Furthermore, positive emotion was found to have a direct and significant effect on impulse buying behavior. These findings reinforce the Stimulus-Organism-Response model, in which flash sales act as a stimulus that evokes emotional responses specifically positive emotions which in turn drive impulsive purchasing behavior. The practical implication of this study highlights the importance of designing promotional strategies that incorporate emotional experiences to enhance the effectiveness and sustainability of digital marketing campaigns.